2020
DOI: 10.1155/2020/4379825
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis between Household Hygiene and Sanitation and Nutritional Status and Female Leprosy in Gresik Regency

Abstract: Leprosy, also known as morbus Hansenʼs disease, is a chronic disease caused by M. leprae. Leprosy attacks various parts of the body including nerves and skin. The most important factor in the occurrence of leprosy is the sources of transmission and contact, both from patients and the environment. Household conditions where the person lives and the nutritional status of the individual can be a risk factor for leprosy. Household hygiene and sanitation can be seen from several aspects, like the physical environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
2
10
1
1
Order By: Relevance
“…Access to proper water is a variable that has no significant effect on the leprosy prevalence on the island of Sulawesi. This result is contrary to the research done by (Prakoeswa et al, 2020), where clean water facilities correlate with the incidence of leprosy in women in Gresik District. The same thing also occurred in the study by Emerson et al, where the absence of access to clean water correlated with the incidence of leprosy in the Ethiopian region (Emerson et al, 2020).…”
Section: Modeling the Leprosy Prevalence Using Spatial Error Modelcontrasting
confidence: 99%
See 2 more Smart Citations
“…Access to proper water is a variable that has no significant effect on the leprosy prevalence on the island of Sulawesi. This result is contrary to the research done by (Prakoeswa et al, 2020), where clean water facilities correlate with the incidence of leprosy in women in Gresik District. The same thing also occurred in the study by Emerson et al, where the absence of access to clean water correlated with the incidence of leprosy in the Ethiopian region (Emerson et al, 2020).…”
Section: Modeling the Leprosy Prevalence Using Spatial Error Modelcontrasting
confidence: 99%
“…In addition, based on research conducted by (Pramesti et al, 2020) in East Java, the clean and healthy lifestyle variable also affects leprosy prevalence. Meanwhile, in the research of (Prakoeswa et al, 2020), it was found that there is a relationship between a house's physical environment, waste disposal facilities, and personal hygiene, which are components of a clean and healthy lifestyle in women with leprosy in Gresik district. Research with similar results was also conducted by (Aprizal et al, 2017), where the cases of leprosy in Pekalongan District are influenced by the condition of the physical environment of the house, where bad environmental conditions make a person's risk of contracting leprosy become greater.…”
Section: Modeling the Leprosy Prevalence Using Spatial Error Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…BMI failed to correlate with the presence of reaction and deformities or multibacillary disease in the reported study (p>0.05). A similar study recruiting female patients from Indonesia also could not establish an association between bad nutrition and leprosy (p=0.008, OR=0.422) [ 11 ]. A previous Indian study reported under-nutrition (BMI<18.5) to be more common in leprosy patients than controls with a significant association between WHO grade 2 disability and under-nutrition; however, no association was established between the number of skin lesions and bacillary load [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The groups at high risk of leprosy are individuals who have poor living standards, poor nutrition, and poor environmental conditions 22 . These are thought to cause dysregulation of the immunity 23 which is very prominent in leprosy endemic areas, and makes leprosy transmission easier.…”
Section: Immune Dysregulation In Leprosymentioning
confidence: 99%